2020
DOI: 10.3390/rs12030387
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aquatic Plants Using Multispectral UAV Imagery and Vegetation Index

Abstract: In this study, aquatic plants in a small reservoir were detected using multispectral UAV (Unmanned Aerial Vehicle) imagery and various vegetation indices. A Firefly UAV, which has both fixed-wing and rotary-wing flight modes, was flown over the study site four times. A RedEdge camera was mounted on the UAV to acquire multispectral images. These images were used to analyze the NDVI (Normalized Difference Vegetation Index), ENDVI (Enhance Normalized Difference Vegetation Index), NDREI (Normalized Difference RedE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…(NIR * − red)/(NIR + red) [54] Normalized green-red difference index (NGRDI) (green − red)/(green + red) [55] Green normalized difference vegetation index (GNDVI) (NIR − green)/(NIR + green) [56,57] Normalized difference red edge index (NDRE) (NIR − red edge)/(NIR + red edge) [58] * NIR, near-infrared.…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
See 1 more Smart Citation
“…(NIR * − red)/(NIR + red) [54] Normalized green-red difference index (NGRDI) (green − red)/(green + red) [55] Green normalized difference vegetation index (GNDVI) (NIR − green)/(NIR + green) [56,57] Normalized difference red edge index (NDRE) (NIR − red edge)/(NIR + red edge) [58] * NIR, near-infrared.…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…As a result of being compared with the actual data of the GNDVI, R 2 = 0.73 and RMSE = 3.41. The NDVI and GNDVI, which showed the most apparent difference between aquatic vegetation and water surface, were reported to be the most effective for detecting aquatic plants [54].…”
Section: Spectral Indices Analysismentioning
confidence: 99%
“…Although the blue channel has vegetation reflectance behavior similar to the red band, it has rarely been used in remote sensing as a vegetation indicator. The same applies to the green band, even though numerous researches have shown that it is better related to vegetation constraints [10]. The information obtained from vegetation indices varies due to spectrally similar features.…”
Section: Figure 1-the Spectral Vegetation Curvementioning
confidence: 95%
“…Different spectral bands can reflect the characteristics of different plants and can be used to effectively distinguish different crops (Xu et al, 2019). Song and Park (2020) used the RedEdge multispectral camera from MicaSense to analyze the spectral characteristics of aquatic plants and found that waterside plants exhibited the highest reflectivity in the NIR band, while floating plants had high reflectivity in the red-edge band.…”
Section: Spectral Sensorsmentioning
confidence: 99%